Studi Filosofis-Teologis tentang Relasi antara Aku dan To Makula dalam Terang Pemikiran Gabriel Marcel - Ivan Sampe Buntu; FX Eko Armada Riyanto; Raymundus I Made Sudhiarsa (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
To makula, literally meaning “a sick person,” is a distinctive concept in Torajan culture referring to a person who has biologically died but whose funeral rites have not yet been completed. Rather than being regarded as dead, the individual continues to be recognized as a relational subject and remains actively integrated into family and communal life through practices such as offering food and drink, speaking to the deceased, and caring for the body within the family house until the funeral ceremony takes place. This study explores the philosophical and theological meaning of the relationship between the self and to makula, examining its existential significance within Torajan anthropology, its influence on everyday life, and its possible religious dimension. Using a qualitative phenomenological approach, the research interprets the lived experience of to makula through Gabriel Marcel’s philosophy, particularly his concepts of being, presence, participation, and interpersonal communion. The findings indicate that to makula embodies an enduring relational existence in which death does not immediately dissolve human relationships but transforms them into a continuing presence sustained through love, memory, communal participation, and spiritual solidarity, thereby revealing a philosophical-theological understanding of personhood that transcends the biological definition of death